Paspalum notatum grass-waste-based adsorbent for Rhodamine B removal from polluted water - Zahir, Abdul (Array, 2020)
The potential of Paspalum notatum grass waste to adsorb Rhodamine B dye from aqueous phase is reported in this research. The grass waste was activated and characterized through various techniques to analyze the chemical (FTIR), morphological (SEMEDX), and thermal (TGA) changes incorporated through the activation process. The pollutant removal efficiency of the raw and modified adsorbents was studied by varying different process parameters in a batch process. The maximum capacity of adsorption which was observed for grass waste and activated grass waste was 54 mg g–1 and 72.4 mg g–1 respectively. Among the various kinetic models, the pseudo-second order model gives the best regression results. However, the intraparticle diffusion-adsorption model showed that the diffusion within pores controlled the adsorption rate. Thermodynamic analysis of this process revealed that Rhodamine B adsorption was endothermic and spontaneous in nature. The results of this study show that grass waste has the potential to be used as an adsorbent for the treatment of colored water.